A Guerra Fria na franquia de jogos eletrônicos Call of Duty (2010–2020) - Durante, Alexandre (2022)
For this course completion work, the main sources will be two video games, audiovisual sources1 called: Call of Duty: Black Ops, released in 2010 on November 9th by the development company Treyarch, and Call of Duty: Black Ops Cold War of the year 2020 also developed by Treyarch, both published by Activision, released on November 13, 2020, being a direct sequel to the game released in 2010. Therefore, there are no influences from other games in the Black Ops series, such as 2, 3 and 4. In these two selected games, we have specific events from the Cold War (1947 - 1991). From them, we aim to analyze how the game represents the selected period, as well as the vision of capitalists and socialists. Electronic games and History became a combination a few decades ago. Several franchises have ventured into working with both, as is the case of the Call of Duty video game franchise or, in a more common translation, a “call to duty”. This franchise began with the first game being released in 2003, with the title Call of Duty, coming from Call of Duty: Finest Hour (2004), Call of Duty 2 (2005) and Call of Duty 3 (2006), which they recreated important battles from the Second World War (1939 - 1945). Another important point is that the player always assumes the role of an allied soldier2, be it North American, British or Soviet (these would become the enemies in the Black Ops series, and Russian enemies in Modern Warfare, post-Cold War period).